Investigation of vibration impact on metrological characteristics of measuring devices in conditions of pump station №5 channel named after Satpayeva; IOP Conference Series: Materials Science and Engineering; Vol. 457 : Modern Technologies for Non-Destructive Testing - Ayzhambayeva S. Zh. (2019, 2019)
Title screen